О кормовых связях гусениц семейства медведиц (Arctiidae) - Павлик, Г.Н. (Вестник зоологии, 1974)
Some peculiarities in ecology of batterfly caterpillars from the Arctiidae family are studied. Natural habitats of caterpillars Arctia caja L., A. villica L., Phragmatobia fuliginosa L. and Hyphantria cunea Dr. are characterized. The fodder selectivity and trophic relations of these species of caterpillars under natural and under experimental conditions are studied as well. Besides, the possibilities for widening the range of folder plants for caterpillars of the Arctiidae family are considered. It was established that in spite of the wide polyphagy under experimental conditions and potential ability of eating various plants under natural conditions, caterpillars of the Arctiidae family prefer relatively few plants.